Insurgent [videorecording (Blu-Ray)] - Schwentke, Robert, 1968-; Woodley, Shailene; James, Theo, 1984-; Winslet, Kate; Trapanese, Joseph; Roth, Veronica (Lionsgate, 2015)
As war surges in the dystopian society around her, Divergent Tris Prior must continue trying to save those she loves, and herself, while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love.